Keterkaitan Antara Hadis dan Politik di Indonesia pada Era Digital (Kajian Hadis Tentang Larangan Memberi Jabatan Bagi Orang yang Meminta Jabatan) - Muhammad Torieq Abdillah; Noor Syifa Humairoh; Anwar Hafidzi; Sulaiman Kurdi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2018)
Abstract: The hadith is one of the guidelines of muslims in the act in addition to the quran, also has a relationship with the travel of the implementation of the political as in Indonesia, especially in terms of power. Especially in this digital era of understanding and to-sharh (explanation) the contents of the hadith is already a little different from time immemorial. Like for example what happened today in Indonesia, the guidelines in politics seems to have forgotten the teachings in the quran and the hadith, with mutual pursuit of office. The purpose of this study was to determine whether the requested post is still relevant today especially in Indonesia using the system of democracy or the shift times will not change in the slightest understanding of the hadith. This research uses the descriptive qualitative method. Data collection techniques in the form of a literature study. The results of this study show that the facts and the reality of what happened in Indonesia often have differences and contrary to the depiction in the hadith, where according to a hadith regarding the provision of office or power, no post for people who ask for a position. While the reality on the political scene in Indonesia opposite happens, where people are a race and seeks to gain power and position which is considered high and features. Abstrak: Hadis yang merupakan salah satu pedoman umat Islam dalam bertindak selain alquran, juga memiliki keterkaitan dengan perjalanan pelaksanaan politik seperti yang ada di Indonesia, khususnya dalam hal kekuasaan. Terlebih di era digital ini pemahaman dan men-syarh (menjelaskan) isi hadis sudah sedikit berbeda dengan zaman dahulu. Seperti contohnya yang terjadi saat ini di Indonesia, pedoman dalam berpolitik sepertinya telah melupakan ajaran dalam alquran maupun hadis, dengan saling mengejar jabatan. Tujuan dari penelitian ini adalah untuk mengetahui apakah meminta jabatan masih relevan di zaman sekarang terkhusus di Indonesia yang menggunakan sistem demokrasi ataukah pergeseran zaman tidak akan merubah sedikit pun pemahaman tentang hadis tersebut. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data berupa studi kepustakaan. Hasil penelitian ini menunjukkan bahwa fakta dan realita yang terjadi di Indonesia sering kali memiliki perbedaan dan bertolak belakang dengan penggambaran di dalam hadis, di mana menurut hadis mengenai pemberian jabatan atau kekuasaan, dilarang memberi jabatan bagi orang yang meminta sebuah jabatan. Sedangkan realita di kancah perpolitikan di Indonesia terjadi sebaliknya, di mana orang berlomba dan berusaha untuk mendapatkan kekuasaan dan jabatan yang dirasa tinggi dan bergengsi.